Nahkämpfe: zur Potentialität von Gewalt in Sibotes ›der vrouwen zuht‹ und ›La Dame escoillee‹ - Tschachtli, Sarina (Beiträge zur Geschichte der deutschen Sprache und Literatur, 2019)
The article explores scenes of violence in Sibote’s ›der vrouwen zuht‹ and ›La Dame escoillee‹, arguing that the texts do not stage male dominance as a natural order (as one might assume), but rather illustrate a shift from violent acts (violentia) to a staging of potential violence that constitutes power (potentia). Whereas acts of violence are immediately visible, the staging of power is more complex, demanding indirect and symbolic forms of force that suggest an unlimited potential for violence. Both texts show these scenes to be effective, attesting to male dominance and thus affirming contemporary gender discourses; at the same time, they uncover just how constructed and staged this position of male power is, thus exposing an artificial rather than a natural order of genders.
Gesehen am 11.02.2020